Neonatal Death in India: Birth Order in a Context of Maternal Undernutrition - Diane Coffey; Dean Spears (Institute of Labor Economics (IZA), 2019)
We document a novel fact about neonatal death, or death in the first month of life. Globally, neonatal mortality is disproportionately concentrated in India. We identify a large effect of birth order on neonatal mortality that is unique to India: later-born siblings have a steep survival advantage relative to the birth order gradient in other developing countries. We show that India's high prevalence of maternal undernutrition and its correlation with age and childbearing can explain this pattern. We find that Indian mothers exit the underweight body mass range at an internationally comparatively high rate as they progress through childbearing careers.
Keywords: O15; I15; 330; neonatal mortality; infant mortality; birth order; maternal nutrition; India